Implementation of Sadd adz-Dzari'ah in the Efforts of Ninik Mamak to Prevent Child Marriage in Nagari Sungai Nanam from the Perspective of Islamic Family Law - Kholidah, Kholidah; Ermansa, Efri; Ummah, Azka (Jurnal El-Thawalib, 2025)
The phenomenon of child marriage remains a serious problem in Indonesia, including in Sungai Nanam Village, Solok Regency, West Sumatra. Although the government has raised the minimum age for marriage through Law Number 16 of 2019 to 19 years for both men and women, the practice of underage marriage continues due to cultural and economic factors, as well as low public legal awareness. This study aims to analyze the role and strategies of ninik mamak in preventing underage marriage and examine these efforts from the perspective of sadd adz-dzari'ah in Islamic family law. The research method is field research with a normative-sociological approach. Primary data were obtained through interviews with traditional leaders, ninik mamak, and village officials; secondary data were sourced from village documents, laws and regulations, and academic literature. Data collection techniques included observation, interviews, and documentation, and the data were analyzed using inductive techniques. The results of the study indicate that ninik mamak have a strategic role in instilling customary and religious values in children and nieces, providing advice, and imposing social sanctions against perpetrators of underage marriage. The strategies implemented include socialization of customs, outreach to educational and health institutions, and collaboration with the KUA and the Nagari government. This effort is in line with the concept of sadd adz-dzari'ah, which aims to close the path to mafsadah (damage), such as domestic violence, early divorce, and reproductive health problems. Thus, the ninik mamak effort is not just a social action but also a means of implementing Islamic legal values in the local Minangkabau context.